Lithium ion battery combining low-temperature discharge and high-temperature cycle
By forming a porous and stable SEI film on the surface of the negative electrode active material of the lithium-ion battery, the problem of difficulty in taking into account both performance in high and low temperature environments is solved, and the excellent performance of the battery in a wider temperature range is achieved, and its application environment is broadened.
Patent Information
- Application Number
- CN202510118998.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-24
AI Technical Summary
Existing lithium-ion batteries are difficult to take into account excellent discharge characteristics and cycling performance in high and low temperature environments, resulting in limited applications.
By forming a porous and stable SEI film on the surface of the negative electrode active material of the lithium-ion battery, the parameters such as the mass percentage of a specific compound in the electrolyte and the ash content of the negative electrode material are used to satisfy specific relationships to improve the low-temperature discharge and high-temperature cycling performance of the battery.
It realizes excellent discharge performance of lithium-ion batteries at low temperatures and stable circulation performance at high temperatures, making the batteries perform well in a wider temperature range and broaden their application environment.
Smart Images

Figure CN119905640A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery that takes both low-temperature discharge and high-temperature circulation into consideration. Background Art
[0002] Due to the advantages of high specific energy, low self-discharge, no memory effect, and high operating voltage, lithium-ion batteries have been widely used in mobile phones, laptops, smart homes, automotive power batteries, large-scale industrialization, and home energy storage. With the growing demand for the battery life, power characteristics, and service life of electronic products, lithium-ion batteries have been developing towards high energy, high safety, and long life.
[0003] Lithium-ion batteries are composed of four main materials: positive electrode, negative electrode, separator and electrolyte. As the application field of lithium-ion batteries continues to expand, the electrochemical performance they pursue is also constantly improving, such as discharge characteristics at low temperatures and service life at high temperatures. However, due to the problem that the electrolyte of lithium-ion batteries is more likely to react with the positive and negative active materials at high temperatures and has a higher resistance at low temperatures, it is generally difficult for the lithium-ion batteries currently used to have both excellent low-temperature discharge characteristics and high-temperature cycle performance.
[0004] Therefore, how to overcome the above-mentioned defect that high and low temperature lithium battery performance cannot be taken into account is a technical problem that urgently needs to be solved in this field.
[0005] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0006] The embodiments of the present disclosure at least provide a lithium-ion battery that takes into account both low-temperature discharge and high-temperature cycling.
[0007] In a first aspect, the present disclosure provides a lithium-ion battery, comprising: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the mass percentage of ash in the negative electrode active material of the negative electrode sheet is H, O I The value is D; the electrolyte includes a compound The mass percentage of the compound in the electrolyte is C1; the compound forms an SEI film on the surface of the negative electrode active material after the first charging cycle of the lithium ion battery; the ratio of the total mass of the electrolyte to the discharge capacity of the lithium ion battery is Ng / Ah; wherein the lithium ion battery satisfies the following relationship: Wherein, R0 is a single bond or a methylene group, R1 is any one of hydrogen, halogen, a hydrocarbon group having 1 to 5 carbon atoms, or a halogenated hydrocarbon group having 1 to 5 carbon atoms, and R2, R3, and R4 are independently selected from Any one of the above, and R2, R3, and R4 are not selected at the same time
[0008] In an optional embodiment, R1 includes any one of hydrogen, halogen, methyl, ethyl, n-propyl, isopropyl, butyl, pentyl, hexyl, halomethyl, haloethyl, halo-n-propyl, haloisopropyl, halobutyl, halopentyl and halohexyl.
[0009] In an optional embodiment, the compound includes at least one of the following compounds:
[0010]
[0011] In an optional embodiment, the ash content is obtained by the ratio of the mass of the remaining material to the initial mass of the negative electrode active material after the negative electrode active material is kept at 900° C. for 16 hours, and satisfies the following relationship: 0.005≤H≤0.03.
[0012] In an optional embodiment, the mass percentage C1% of the compound in the electrolyte satisfies the following relationship: 0.1%≤C1≤3%.
[0013] In an optional embodiment, the O I The value is obtained by XRD test using the ratio of the (004) diffraction peak intensity to the (110) diffraction peak intensity and satisfies the following relationship: 1≤D≤10.
[0014] In an optional implementation, the discharge capacity of the lithium-ion battery is obtained by discharging the battery at 0.5C to a cut-off voltage after the battery is fully charged, and the ratio N satisfies the following relationship: 1≤N≤3.
[0015] In an optional embodiment, the mass proportion of sulfur in the SEI film is 0.1% to 0.8%.
[0016] In an optional embodiment, the electrolyte further includes an electrolyte salt, and the mass proportion of the electrolyte salt in the electrolyte is 10% to 20%.
[0017] In an optional embodiment, the electrolyte further includes an additive, and the mass proportion of the additive in the electrolyte is 1% to 10%; the additive includes at least one of vinylene carbonate, methylene disulfonate, 1,3-propane sultone, glycerol trinitrile, succinonitrile, adiponitrile, 1,3,6-hexane trinitrile, fluoroethylene carbonate, lithium bis(fluorooxalatoborate), lithium bis(oxalatoborate), lithium tetrafluoroborate and lithium bis(fluorobis(oxalatophosphate)).
[0018] The beneficial effect of the present invention is that the compound of the lithium-ion battery that takes into account both low-temperature discharge and high-temperature cycling can form an effective SEI film on the surface of the negative electrode active material during the first charging and cycling of the battery under the premise of satisfying various relationship equations, and has porous and stable characteristics, thereby improving the low-temperature discharge and high-temperature cycling performance of the lithium-ion battery, taking into account the defects at two extreme temperatures, and broadening the application environment of the lithium-ion battery.
[0019] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description.
[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below for detailed description as follows. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In this document, a single "compound" refers specifically to The specific structures of its different substituents can also be referred to as Formula 1 in specific embodiments, and do not refer to all compounds.
[0023] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0024] In this document, as used herein, expressions such as "at least one of..." when following a list of elements modify the entire list of elements rather than modifying the individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0025] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0026] Some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0027] The present disclosure provides a lithium-ion battery, comprising: a positive electrode plate, a negative electrode plate, a separator and an electrolyte; the mass percentage of ash in the negative electrode active material of the negative electrode plate is H, O I The value is D; the electrolyte includes a compound The mass percentage of the compound in the electrolyte is C1; the compound forms an SEI film on the surface of the negative electrode active material after the first charging cycle of the lithium ion battery; the ratio of the total mass of the electrolyte to the discharge capacity of the lithium ion battery is Ng / Ah; wherein the lithium ion battery satisfies the following relationship: Wherein, R0 is a single bond or a methylene group, R1 is any one of hydrogen, halogen, a hydrocarbon group having 1 to 5 carbon atoms, or a halogenated hydrocarbon group having 1 to 5 carbon atoms, and R2, R3, and R4 are independently selected from Any one of the above, and R2, R3, and R4 are not selected at the same time
[0028] Specifically, this is because N determines the mass of the electrolyte retained in the lithium-ion battery, and C1 determines the mass of the compound in the retained electrolyte mass. The two largely determine the number or number of compound molecules present in the lithium-ion battery. H and D largely affect the number of molecules required for the compound to form the SEI film. When the above formula relationship is satisfied between them, the number of molecules of the compound in the lithium-ion battery can just form a complete SEI film, and at the same time can supplement the appropriate amount of consumption under subsequent high-temperature cycles. As a result, the battery has excellent low-temperature discharge performance and high-temperature cycle performance.
[0029] In some embodiments, specifically, the R1 includes any one of hydrogen, halogen, methyl, ethyl, n-propyl, isopropyl, butyl, pentyl, hexyl, halogenated methyl, halogenated ethyl, halogenated n-propyl, halogenated isopropyl, halogenated butyl, halogenated pentyl and halogenated hexyl. During the first charge and cycle of the battery, the compound can be reduced on the surface of the negative electrode active material in priority to the electrolyte solvent to form a SEI film rich in sulfonate-containing compounds. The formed SEI film is relatively thin, which is conducive to the rapid passage of ions during the charge and discharge process, so the impedance of the SEI film is low, thereby effectively improving the kinetic performance of the battery. The formed SEI film has high stability and can inhibit the further decomposition of the electrolyte during charge and discharge at high temperatures, thereby effectively improving the high-temperature cycle performance of the battery.
[0030] In some embodiments, specifically, the compound includes at least one of the following compounds:
[0031]
[0032] In some embodiments, specifically, the ash content is obtained by the ratio of the mass of the remaining material to the mass of the initial material after the negative electrode active material is kept at 900°C for 16 hours, and satisfies the following relationship: 0.005≤H≤0.03; the ash content of the negative electrode material includes metal elements and inorganic element impurities, which will catalyze the decomposition of the electrolyte; the larger the H, the more electrolyte will be consumed, resulting in a high-impedance SEI film. Therefore, controlling H within a certain range will improve the low-temperature discharge performance of the battery.
[0033] In some embodiments, specifically, the mass percentage C1% of the compound in the electrolyte satisfies the following relationship: 0.1%≤C1≤3%; the size of N determines to a certain extent the number of molecules of the compound represented by Formula 1 contained in the battery and the concentration of each molecule in the electrolyte. During the first charge, C1 determines the frequency of the compound appearing on the surface of the negative electrode. The larger the C1, the greater the activity of the compound. The greater the frequency of appearance on the surface of the negative electrode, the more S-rich SEI film will be formed on the negative electrode. The SEI film has low impedance and high stability. In this way, both the low-temperature discharge performance and the high-temperature cycle performance of the battery can be taken into account at the same time.
[0034] In some embodiments, specifically, the I The value is obtained by XRD test using the ratio of the (004) diffraction peak intensity to the (110) diffraction peak intensity, and satisfies the following relationship: 1≤D≤10; the larger the D, the larger the negative electrode surface area, the larger the contact area with the electrolyte, and the more compound molecules will be required. Therefore, controlling D within a certain range can improve the high-temperature cycle performance of the battery.
[0035] In some embodiments, specifically, the discharge capacity of the lithium-ion battery is obtained by discharging the battery at 0.5C to a cut-off voltage after the battery is fully charged, and the ratio N satisfies the following relationship: 1≤N≤3; the size of N determines the mass of electrolyte in the battery, which to a certain extent determines the mass or molar number of compounds in the electrolyte, which will affect the thickness of the SEI film when the battery is charged for the first time. The larger the N, the thicker the SEI film, which will significantly improve the low-temperature performance of the battery. In this way, the low-temperature discharge performance of the battery can be improved.
[0036] In some embodiments, specifically, the mass proportion of sulfur in the SEI film is 0.1% to 0.8%, and the proportion of sulfur is tested by an X-ray photoelectron spectrometer at a sputtering etching time of 0 seconds.
[0037] In some embodiments, specifically, the negative electrode active material of the negative electrode plate includes graphite or silicon-based materials.
[0038] In some embodiments, specifically, the silicon-based material may include at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, and silicon alloys.
[0039] Specifically, the negative electrode plate further includes a negative electrode current collector, a first adhesive and a first conductive agent.
[0040] In some embodiments, specifically, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0041] In some embodiments, specifically, the first binder may include at least one of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0042] In some embodiments, specifically, the first conductive agent may include at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.
[0043] In some embodiments, specifically, the mass ratio of the negative electrode active material, the first conductive agent, and the first binder is (90-99):(0-5):(1-10).
[0044] In some embodiments, specifically, the positive electrode active material of the positive electrode plate includes lithium iron phosphate material, nickel-cobalt-manganese ternary material, lithium cobalt oxide material, lithium manganese iron phosphate material, lithium manganese oxide material or nickel-manganese oxide lithium material.
[0045] Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes at least one of a second binder and a second conductive agent and a positive electrode active material.
[0046] In some embodiments, specifically, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0047] In some embodiments, specifically, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0048] In some embodiments, specifically, when the battery is a lithium-ion battery, the positive electrode active material includes, but is not limited to, lithium iron phosphate material, LiCoO2 material, LiNiO2, nickel cobalt manganese ternary material (LiNi x Co y Mn z O2 (x + y + z = 1, 0 < x < 1, 0 < y < 1, 0 < z < 1)), lithium-rich manganese-based material (nLi2MnO3(1 - n)LiMO2(0 < n < 1, M is one, two or three of Ni, Co, Mn)), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) material, lithium manganese phosphate material, lithium manganate material, lithium nickel manganese oxide material, etc. Preferably, the lithium iron phosphate material, nickel cobalt manganese ternary material, lithium cobalt oxide material, lithium manganese phosphate material, lithium manganate material or lithium nickel manganese oxide material has excellent cycle performance and high energy density, thereby improving the cycle stability of the battery.
[0049] In some embodiments, specifically, the second conductive agent includes at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber.
[0050] In some embodiments, specifically, the second binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride (PVDF), polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, methyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polymers containing ethylene oxide, polyvinyl pyrrolidone, and polyurethane.
[0051] In some embodiments, specifically, the mass ratio of the positive electrode active material, the second conductive agent, and the second binder is (90 - 99.5):(0.25 - 5):(0.25 - 5).
[0052] In some embodiments, specifically, the electrolyte solvent includes at least one of carbonates (such as cyclic carbonates and chain carbonates), carboxylates (such as cyclic carboxylates and chain carboxylates), ether compounds (such as cyclic ether compounds and chain ether compounds), phosphorus-containing compounds, sulfur-containing compounds, and aromatic fluorine-containing compounds.
[0053] In some embodiments, specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), propyl butyrate (PB), ethyl butyrate (EB), propyl propionate (PP), ethyl propionate (EP), methyl propionate (MP), propyl acetate (PA), ethyl acetate (EA), methyl acetate (MA), propyl formate (PF), ethyl formate (EF), methyl formate (MF), and γ-butyrolactone.
[0054] In some embodiments, specifically, the electrolyte further includes an electrolyte salt, and the mass proportion of the electrolyte salt in the electrolyte is 10% to 20%.
[0055] In some embodiments, specifically, the electrolyte salt is preferably a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0056] In some embodiments, specifically, the electrolyte further includes an additive, and the mass proportion of the additive in the electrolyte is 1% to 10%; the additive includes at least one of vinylene carbonate, methylene disulfonate, 1,3-propane sultone, glycerol trinitrile, succinonitrile, adiponitrile, 1,3,6-hexane trinitrile, fluoroethylene carbonate, lithium bis(fluorooxalatoborate), lithium bis(oxalatoborate), lithium tetrafluoroborate and lithium bis(fluorobis(oxalatophosphate)).
[0057] In some embodiments, specifically, the battery further includes a separator, which includes but is not limited to glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.
[0058] Example 1
[0059] (1) Preparation of electrolyte: In an inert atmosphere (water <0.1ppm, oxygen <1ppm), ethylene carbonate (EC), propyl propionate (PP) and diethyl carbonate (DEC) are mixed in a mass ratio of EC:PP:DEC=3:3:4. After mixing evenly, lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) are added, and the mass proportion of LiFSI in the electrolyte is 2wt%, and the mass proportion of LiPF6 in the electrolyte is 15wt%. Then, the compound of formula 1-1 is added, and the mass proportion of the compound of formula 1-1 is 2wt% based on the total mass of the electrolyte.
[0060] (2) Preparation of positive electrode sheet: Lithium cobalt oxide, acetylene black and poly (vinylidene fluoride) are dispersed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 97:1:2, and the mixture is stirred thoroughly to form a uniform positive electrode slurry, which is then evenly coated on the positive electrode current collector aluminum foil. After drying, rolling and slitting, the positive electrode sheet is obtained.
[0061] (3) Preparation of negative electrode sheet: Graphite, acetylene black, sodium carboxymethyl cellulose and styrene butadiene rubber (SBR) were dispersed in an appropriate amount of deionized water at a mass ratio of 95:2:2:1, and the mixture was fully stirred to form a uniform negative electrode slurry, which was then evenly coated on the negative electrode current collector copper foil. After drying, rolling and cutting, the negative electrode sheet was obtained. The ash content H% of the graphite material was 0.01wt%. I The value D is 2.
[0062] (4) Preparation of battery: stack the positive electrode sheet, separator and negative electrode sheet in order, place the separator between the positive electrode sheet and the negative electrode sheet to play an isolating role, then wind to obtain a battery cell, and place the bare battery cell in an outer packaging shell, after drying, inject the electrolyte prepared in step (1), the total mass of the electrolyte is 7.7g. After vacuum packaging, standing, forming, shaping and other processes, the preparation of the battery is completed, and its rated capacity is 5.5Ah, and the ratio of the total mass of the electrolyte to the discharge capacity of the battery is Ng / Ah is 1.4 / Ah. Specifically, the capacity of the battery after being fully charged at a current of 0.5C and then fully discharged at a current of 0.5C is 5.5Ah.
[0063] Example 2
[0064] The difference between Example 2 and Example 1: The compound represented by Formula 1 used in Example 2 is Formula 1-2.
[0065] Example 3
[0066] The difference between Example 3 and Example 1: The compound represented by Formula 1 used in Example 3 is Formula 1-3.
[0067] Example 4
[0068] The difference between Example 4 and Example 1: The compound represented by Formula 1 used in Example 4 is Formula 1-4.
[0069] Example 5
[0070] The difference between Example 5 and Example 1: The compound represented by Formula 1 used in Example 5 is Formula 1-5.
[0071] Example 6
[0072] The difference between Example 6 and Example 1: The compound represented by Formula 1 used in Example 6 is Formula 1-6.
[0073] Example 7
[0074] The difference between Example 7 and Example 1: The compound represented by Formula 1 used in Example 7 is Formula 1-7.
[0075] Example 8
[0076] The difference between Example 8 and Example 1 is that the ratio of the total mass of the electrolyte in Example 8 to the discharge capacity of the battery is 1 g / Ah.
[0077] Example 9
[0078] The difference between Example 9 and Example 1 is that the ratio of the total mass of the electrolyte in Example 9 to the discharge capacity of the battery is 3 g / Ah.
[0079] Example 10
[0080] The difference between Example 10 and Example 1: The mass proportion C1 of the compound of formula 1-1 in Example 10 is 0.1 wt%.
[0081] Embodiment 11
[0082] The difference between Example 11 and Example 1: The mass proportion C1 of the compound of formula 1-1 in Example 11 is 3wt%.
[0083] Example 12
[0084] The difference between Example 12 and Example 1 is that the graphite in Example 12 has I The value D is 1.
[0085] Embodiment 13
[0086] The difference between Example 13 and Example 1 is that the graphite in Example 13 has I The value D is 10.
[0087] Embodiment 14
[0088] The difference between Example 14 and Example 1: The ash content H% of the graphite in Example 14 is 0.005wt%.
[0089] Embodiment 15
[0090] The difference between Example 15 and Example 1: The ash content H% of the graphite in Example 15 is 0.03wt%.
[0091] Example 16
[0092] The difference between Example 16 and Example 1: In the electrolyte of Example 16, 3% of 1,3,6-hexanetricarbonitrile (HTCN) is further added in the preparation of the electrolyte in step (1).
[0093] Embodiment 17
[0094] The difference between Example 17 and Example 1: The positive electrode active material in step (2) of Example 17 is LiNi 0.5 Co 0.2 Mn 0.3 O2.
[0095] Comparative Example 1
[0096] The difference between Comparative Example 1 and Example 1 is that the aforementioned compound is not added to the electrolyte of Comparative Example 1.
[0097] Comparative Example 2
[0098] The difference between Comparative Example 2 and Example 1 is as follows: Based on the total mass of the electrolyte, the mass proportion of the above-mentioned compound C1 is 0.2w%, the ash content H% of the graphite material is 0.03wt%, and the O I The value D is 1. The ratio of the total mass of the electrolyte to the discharge capacity of the battery, Ng / Ah, is 1 g / Ah.
[0099] Comparative Example 3
[0100] The difference between Comparative Example 3 and Example 1 is as follows: In the electrolyte of Comparative Example 3, based on the total mass of the electrolyte, the mass proportion of the above-mentioned compound C1 is 3wt%. The ash content H% of the graphite material is 0.005wt%, and the O I The value D is 10. The ratio Ng / Ah of the total mass of the electrolyte to the discharge capacity of the battery is 3 g / Ah.
[0101] The electrolyte, negative electrode active material and positive electrode active material of Examples 1-17 and Comparative Examples 1-3 are different, as shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] The batteries prepared in Examples 1-17 and Comparative Examples 1-3 were subjected to high temperature cycle tests and low temperature discharge performance tests. The specific test conditions are as follows:
[0106] High temperature cycle test: Place the battery at 45°C and use 1C current for charge and discharge cycles. Record the maximum capacity of the first three times as Q, and select the capacity after 500 cycles as Q2. Calculate the capacity retention rate of the battery after high temperature cycling using the following formula: Capacity retention rate (%) = Q2 / Q×100.
[0107] Low temperature discharge performance test: Charge and discharge the battery once at room temperature with a current of 1C, and record the discharge capacity Q3. Then, fully charge the battery with a current of 1C, and then place the battery in a -20℃ constant temperature box for 4 hours, and discharge it with a current of 0.5C to the lower limit voltage, and record the discharge capacity Q4. Calculate the low temperature discharge capacity retention rate of the battery by the following formula: Low temperature discharge capacity retention rate (%) = Q4 / Q3×100.
[0108] The batteries prepared in Examples 1-17 and Comparative Examples 1-3 were disassembled after capacity division. The negative electrode sheets were cleaned three times with DMC and vacuum-baked at 60°C for 6 hours. The sulfur content of the negative electrode sheets was tested by X-ray photoelectron spectrometer at a sputtering etching time of 0 seconds to obtain the sulfur content in the SEI film.
[0109] The high temperature cycle test, low temperature discharge performance and sulfur content in the SEI film of the batteries prepared in Examples 1-17 and Comparative Examples 1-3 are shown in Table 2.
[0110] Table 2
[0111]
[0112] From the data in Table 2, it can be seen that the high temperature cycle retention rate and low temperature discharge retention rate of the batteries of Examples 1-17 are significantly improved compared with the battery of Comparative Example 1 without adding the compound shown in Formula 1. In particular, although the values calculated by adding Formula 1 are not between 0.02 and 2.1 in Comparative Examples 2 and 3, the high temperature cycle retention rate and low temperature discharge retention rate of the batteries are much lower than those of Examples 1-20, indicating that not only the aforementioned compounds are added to the electrolyte of the present application, but also the values calculated by the above formula are between 0.02 and 2.1, and the final battery has excellent low temperature discharge performance and high temperature cycle stability.
[0113] In summary, the compound of the lithium-ion battery that takes into account both low-temperature discharge and high-temperature cycling can form an effective SEI film on the surface of the negative electrode active material during the first charging and cycling of the battery under the premise of satisfying various relationship equations, and has porous and stable characteristics, thereby improving the low-temperature discharge and high-temperature cycling performance of the lithium-ion battery, taking into account the defects at two extreme temperatures, and broadening the application environment of lithium-ion batteries.
[0114] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A lithium ion battery, characterized in that: include: Positive electrode sheet, negative electrode sheet, separator and electrolyte; The mass percentage of ash in the negative electrode active material of the negative electrode plate is H, O I The value is D; The electrolyte includes a compound And the mass percentage of the compound in the electrolyte is C1; The compound forms a SEI film on the surface of the negative electrode active material after the first charging cycle of the lithium ion battery; The ratio of the total mass of the electrolyte to the discharge capacity of the lithium-ion battery is N g / Ah; Wherein, the lithium-ion battery satisfies the following relationship: Wherein, R0 is a single bond or a methylene group, R1 is any one of hydrogen, halogen, a hydrocarbon group having 1 to 5 carbon atoms, or a halogenated hydrocarbon group having 1 to 5 carbon atoms, and R2, R3, and R4 are independently selected from Any one of the above, and R2, R3, and R4 are not selected at the same time 2. The lithium-ion battery according to claim 1, characterized in that The R1 includes any one of hydrogen, halogen, methyl, ethyl, n-propyl, isopropyl, butyl, pentyl, hexyl, halogenated methyl, halogenated ethyl, halogenated n-propyl, halogenated isopropyl, halogenated butyl, halogenated pentyl and halogenated hexyl.
3. The lithium ion battery according to claim 1, characterized in that The compound comprises at least one of the following compounds:
4. The lithium ion battery according to claim 1, characterized in that The ash content is obtained by the ratio of the mass of the remaining material to the mass of the initial material after the negative electrode active material is kept at 900° C. for 16 hours, and satisfies the following relationship: 0.005≤H≤0.03。 5. The lithium ion battery according to claim 1, characterized in that The mass percentage C1% of the compound in the electrolyte satisfies the following relationship: 0.1%≤C1≤3%。 6. The lithium ion battery according to claim 1, characterized in that The O I The value is obtained by XRD test using the ratio of the (004) diffraction peak intensity to the (110) diffraction peak intensity and satisfies the following relationship: 1≤D≤10。 7. The lithium ion battery according to claim 1, characterized in that The discharge capacity of the lithium-ion battery is obtained by discharging the battery at 0.5C to the cut-off voltage after the battery is fully charged, and the ratio N satisfies the following relationship: 1≤N≤3。 8. The lithium ion battery according to claim 1, characterized in that The mass proportion of sulfur in the SEI film is 0.1% to 0.8%.
9. The lithium ion battery according to claim 1, characterized in that The electrolyte solution further includes an electrolyte salt, and the mass proportion of the electrolyte salt in the electrolyte solution is 10% to 20%.
10. The lithium ion battery according to claim 1, characterized in that The electrolyte further includes an additive, and the mass proportion of the additive in the electrolyte is 1% to 10%; The additive includes at least one of vinylene carbonate, methylene methanedisulfonate, 1,3-propane sultone, glycerol trinitrile, succinonitrile, adiponitrile, 1,3,6-hexane trinitrile, fluoroethylene carbonate, lithium bisfluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate and lithium bisfluorobisoxalatophosphate.
Citation Information
Patent Citations
Secondary battery and device
CN117525594A
Battery
CN118867379A
Non-aqueous electrolyte solution for secondary cell and non-aqueous electrolyte secondary battery employing the same
JP2007184257A